4E analysis of a SOFC-CCHP system with a LiBr absorption chiller. (November 2022) - Xu, Yuhao; Luo, Xiaobing; Tu, Zhengkai
Abstract: A new system which combined cooling, heating and power (CCHP) and based on a solid oxide fuel cell (SOFC) with a LiBr absorption chiller and water tank is investigated. The influence of the working conditions of the SOFC on its steady-state and dynamic performances are studied. Meanwhile, the effects of working conditions of the stack and absorption chillers on multi-criteria assessments are also studied. The result shows that the operating temperature and current density can greatly affect the performance of the stack and system, which can also be influenced by the working conditions of the absorption chiller simultaneously. Increasing the operating temperature can greatly increase the electrical power, and the thermal power will be reduced correspondingly. Increasing the mass flows of the cooling, chilled and hot waters increase the cooling power and coefficient of performance (COP), thereby reducing the heating power. Highlights: A SOFC-based CCHP system with a LiBr absorption chiller is proposed. The steady-state and dynamic characteristics of the stack are investigated. The thermal, economic and environmental performance of the system are performed. The electrical power is the largest when current density reaches 564.75 mA ⋅ cm -2 .